Leksikal Q?la [ ??? ] dalam Dialog Naratif al-Quran: Penelitian Makna Komunikatif Terjemahan Melayu Lexical Q?la [ ??? ] in Qur’anic Narrative Dialogues: An Analysis of Communicative Meaning in Malay Translation (KEMANUSIAAN The Asian Journal of Humanities, 2019)
Translation is a communication tool that involves cross-cultural meaning. Therefore, the correct meaning of a translated linguistic form alone does not guarantee smooth communication, particularly in dialogues. This study focuses on the translation of the lexical form q?la [ ??? ] in Qur’anic dialogues into Malay. The lexical form is often translated into Malay as “berkata”, “berfirman” and “bersabda” (said/has said). The study is informed by the semantic translation theory and the communicative translation theory frameworks by Newmark. The objective of this study is to identify and evaluate the translation of lexical q?la and its derivation in selected Qur’anic dialogues. Based on data extracted from surah al-Kahf, a descriptive analysis of the dialogues containing the lexical form q?la [ ??? ] shows that it is translated as “berkata” (said/has said) in many instances (48.2 percent) and as “ujar”, “berfirman” and “berdoa” the rest of the time. A contrastive analysis and evaluation of the narrative translation of the dialogues suggests that there is room for strengthening these lexical translations based on the communicative translation theory. This is so that Qur’anic dialogues could be presented more interestingly and effectively. Terjemahan merupakan wahana komunikasi yang melibatkan silang budaya dan penyampaian makna. Dalam proses penterjemahan, dua bahasa atau lebih digandingkan untuk mencapai satu makna yang disepakati. Makna yang betul sahaja secara relatifnya tidak menjamin komunikasi yang lancar dalam interaksi, khususnya dialog. Oleh itu, kajian ini memfokus pada terjemahan leksikal q?la [ ??? ] dalam dialog al-Quran yang sering diterjemahkan sebagai “berkata”, “berfirman” dan “bersabda”. Kerangka teori terjemahan semantik dan teori terjemahan komunikatif oleh Newmark dan makna konteks dijadikan landasan kajian memandangkan al-Quran adalah sumber berwibawa yang sesuai dengan teori yang disebutkan. Objektif kajian ini ialah untuk mengenal pasti dan menilai terjemahan leksikal q?la dan derivasinya dalam al-Quran. Berdasarkan data yang dikutip daripada surah al-Kahf, analisis deskriptif terhadap dialog yang mengandungi 10 leksikal q?la menunjukkan terjemahan cenderung menterjemahkan leksikal q?la sebagai “berkata” dengan jumlah 48.2 peratus dan selebihnya menggunakan padanan daripada pelbagai variasi seperti “ujar”, “berfirman” dan “berdoa”. Analisis kontrastif dan penilaian terhadap terjemahan naratif dialog pula mendapati masih ada ruang untuk memantapkan terjemahan leksikal ini berdasarkan Teori Terjemahan Komunikatif agar dialog dalam al-Quran dapat dipersembahkan dalam naratif yang lebih menarik dan berkesan.